Upregulation of Amy1 in the salivary glands of mice exposed to a lunar gravity environment using the multiple artificial gravity research system - Ouchi, Takehito; Kono, Kyosuke; Satou, Ryouichi; Kurashima, Ryuya; Yamaguchi, Koji; Kimura, Maki; Shibukawa, Yoshiyuki (Frontiers in Physiology, 2024)
Introduction: Space is a unique environment characterized by isolation from community life and exposure to circadian misalignment, microgravity, and space radiation. These multiple differences from those experienced on the earth may cause systemic and local tissue stress. Autonomic nerves, including sympathetic and parasympathetic nerves, regulate functions in multiple organs. Saliva is secreted from the salivary gland, which is regulated by autonomic nerves, and plays several important roles in the oral cavity and digestive processes. The balance of the autonomic nervous system in the seromucous glands, such as the submandibular glands, precisely controls serous and mucous saliva. Psychological stress, radiation damage, and other triggers can cause an imbalance in salivary secretion systems. A previous study reported that amylase is a stress marker in behavioral medicine and space flight crews; however, the detailed mechanisms underlying amylase regulation in the space environment are still unknown. Methods: In this study, we aimed to elucidate how lunar gravity (1/6 g) changes mRNA expression patterns in the salivary gland. Using a multiple artificial gravity research system during space flight in the International Space Station, we studied the effects of two different gravitational levels, lunar and Earth gravity, on the submandibular glands of mice. All mice survived, returned to Earth from space, and their submandibular glands were collected 2 days after landing. Results: We found that lunar gravity induced the expression of the salivary amylase gene Amy1; however, no increase in Aqp5 and Ano1, which regulate water secretion, was observed. In addition, genes involved in the exocrine system, such as vesicle-associated membrane protein 8 (Vamp8) and small G proteins, including Rap1 and Rab families, were upregulated under lunar gravity. Conclusion: These results imply that lunar gravity upregulates salivary amylase secretion via Rap/Rab signaling and exocytosis via Vamp8. Our study highlights Amy1 as a potential candidate marker for stress regulation in salivary glands in the lunar gravity environment.